Becoming Trauma Informed: Validating a Tool to Assess Health Professional’s Knowledge, Attitude, and Practice - King, Simmy (Pediatr Qual Saf, 2019)
To effectively address the negative health effects of early childhood trauma and adversity, healthcare professionals and healthcare institutions must understand the impact of adverse childhood experiences and trauma on health. This study aimed to validate a tool to assess knowledge, attitude, and practice of trauma-informed care among interdisciplinary pediatric healthcare staff. METHODS: A 36-item survey tool, “Knowledge, Attitudes, and Practices of Trauma-Informed Practice,” was adopted and modified with permission from the author. We administered the survey electronically to 2,659 staff at a pediatric healthcare institution. To assess the tool’s reliability and validity, internal consistency reliability testing, content validity, and construct validity assessments were conducted. RESULTS: A total of 592 surveys were collected, representing a 22.3% response rate. Confirmatory factor analysis revealed that 21 items provided the strongest internal consistency reliability for the overall tool and each factor. The overall Cronbach’s alpha for the 21-item tool was 0.86, with 0.84 for the knowledge factor, 0.74 for the attitude factor, and 0.78 for the practice factor. The goodness of fit based on this analysis was good to adequate, with a 0.077 root mean square error of approximation. CONCLUSIONS: Healthcare professionals and organizations are in a unique position to improve the health and well-being of their patients by implementing a trauma-informed approach to minimize the impact of adverse childhood experiences and trauma. This validated tool will allow organizations to identify gaps in knowledge, attitude, and practice among staff to subsequently begin developing pointed strategies to achieve a culture of trauma-informed practice.